Content Analysis of Information In Local Government Financial Statements and Their Determinants - Loili, Husni; Abdullah, Syukriy (Green Publisher Indonesia, 2023)
This research aims to determine the influence of expenditure variations, government size, and fiscal distress on the information content in the financial reporting of local governments. The study was conducted on 23 local governments in Aceh, using multiple linear regression analysis with SPSS 25. The data were extracted from audited financial reports of local governments for the period 2017-2021. The results indicate that, in the simultaneous test, expenditure variations, local government size, and fiscal distress collectively affect information content. Partially, in the first model, fiscal distress has a positive impact, but expenditure variations and local government size do not affect the information content variable (surplus/deficit difference in LO and LRA). In the second model, expenditure variations have a negative impact, local government size has a positive impact, but fiscal distress does not affect the information content variable (income difference in LRA and LO). In the third model, local government size has a negative impact on the information content variable (expense difference in LO and expenditure in LRA), but expenditure variations and fiscal distress do not affect the information content variable (expense difference in LO and expenditure in LRA).